Synthesis, characterization, and immunological properties in mice of conjugates composed of detoxified lipopolysaccharide of Salmonella paratyphi A bound to tetanus toxoid with emphasis on the role of O acetyls. - Konadu, E (1996)
Salmonella paratyphi A, the second most common cause of enteric fever in Southeast Asia, is a habitant of and a pathogen for humans only. Lipopolysaccharides (LPS) are both essential virulence factors and protective antigens for systemic infections caused by groups A, B, C, and D nontyphoidal salmonellae. The O-specific polysaccharide of S. paratyphi A is composed of a trisaccharide, -->2-alpha-D)-Manp-(1-->4)-alpha-L-Rhap-(1-->3)-alpha-D-Galp -(1-->, with a branch of D-paratose from the C-3 of alpha-D-mannose, and the C-3 of beta-L-rhamnose is partially O acetylated (C. G. Hellerqvist, B. Lindberg, K. Samuelsson, and A. A. Lindberg, Acta Chem. Scand. 25:955-961, 1971). On the basis of data from our investigational vaccines for enteric bacterial pathogens, including group B salmonellae (D. C. Watson, J. B. Robbins, and S. C. Szu, Infect. Immun. 60:4679-4686, 1992), conjugates composed of the detoxified LPS of S. paratyphi A bound to tetanus toxoid (TT) were prepared by several schemes. LPS was detoxified with acetic acid or with hydrazine; the latter removed O acetyls from the O-specific polysaccharide. The detoxified polysaccharides were activated with cyanogen bromide (CNBr) or with 1-cyano-4-dimethylaminopyridinium tetratfluoroborate (CDAP) and bound to TT with or without a spacer. Solutions of 2.5 microgram of saccharide, alone or as a conjugate, were injected subcutaneously into young mice, and LPS and TT antibodies were measured by enzyme-linked immunosorbent assaying. A conjugate synthesized with higher-molecular-weight O-SP elicited the highest anti-LPS levels. Only conjugates with O acetyls elicited serum immunoglobulin G anti-LPS with bactericidal activity. There were no statistically significant differences between LPS antibody levels elicited by conjugates synthesized with or without a spacer. The conjugate with O-specific polysaccharide activated by CDAP and bound to TT without a spacer elicited the highest level of TT antibodies. Clinical evaluation (if S. paratyphi A conjugates is planned.